Effect of Purple Leaf (Graptophyllum pictum (L.) Griff) Emulsion on the Histological Parameters of Streptozotocin-Induced Diabetic Rats - Niluh Puspita Dewi; Komang Dewik; Syafika Alaydrus; Athia Kurnia Kasim; Nani Astria Polontalo; Wayan Wirawan; Dian Andini; Irma Irma; Imelda Synthia Fatu (Jurnal Penelitian Pendidikan IPA, 2026)
Damage to vital organs such as the liver, kidneys, and pancreas is a common complication of diabetes mellitus, characterized by chronic hyperglycemia due to pancreatic cell dysfunction. Graptophyllum pictum (purple leaf) is a potential herbal therapy containing bioactive compounds with antioxidant and organ-protective effects. This study aimed to evaluate the effect of purple leaf emulsion on blood glucose levels and the histopathological features of diabetic rats induced by streptozotocin. Rats were divided into six groups: normal control, negative control, positive control (glibenclamide), and three doses of purple leaf emulsion (100, 200, and 300 mg/kg BW). After 28 days of treatment, the emulsion significantly reduced blood glucose levels and improved the histological structures of the liver, kidneys, and pancreas. The 200 mg/kg BW dose was most effective for pancreatic protection, while 300 mg/kg BW provided optimal hepatoprotective and renoprotective effects. These findings highlight the potential of purple leaf as a natural antidiabetic and organ-protective agent.